KEBERHASILAN IMPLEMENTASI KURIKULUM DALAM PERSPEKTIF MANAJEMEN PENDIDIKAN - Rodhiah, Saniatur; Ikram Shiddiq, Muhammad; Mutmainna Sari, Suci; Nursalim, Eko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the success of curriculum implementation from an educational management perspective through a qualitative literature review focusing on leadership, learning media, instructional strategies, teacher performance, and curriculum monitoring. Ongoing curriculum reforms that demand managerial and pedagogical adaptation constitute the central issue of this research. The study employed a qualitative library research approach by analyzing relevant national and international scholarly articles published between 2020 and 2026 and indexed in academic databases. Data were collected through documentation techniques and analyzed using thematic analysis, including data reduction, categorization, and conceptual synthesis. The findings identified five major themes: (1) instructional leadership as the driving force of implementation, (2) optimization of digital and contextual learning media, (3) adaptive student-centered instructional strategies, (4) strengthening teacher performance through professional learning communities, and (5) reflective, data-based curriculum monitoring and evaluation. The results indicate that successful curriculum implementation is not merely determined by policy or document changes, but by the systemic integration of managerial functions and pedagogical practices within a collaborative school culture. Theoretically, this study enriches the literature by proposing a holistic and integrative framework of curriculum management. Practically and at the policy level, the findings highlight the importance of strengthening instructional leadership, enhancing teacher capacity, and establishing sustainable monitoring systems. Future research is recommended to empirically test the proposed conceptual model across diverse educational contexts to broaden the generalizability of the findings.